Pooled‐matrix protein interaction screens using Barcode Fusion Genetics. Issue 4 (23rd April 2016) - Yachie, Nozomu; Petsalaki, Evangelia; Mellor, Joseph C; Weile, Jochen; Jacob, Yves; Verby, Marta; Ozturk, Sedide B; Li, Siyang; Cote, Atina G; Mosca, Roberto; Knapp, Jennifer J; Ko, Minjeong; et al.
Abstract: High‐throughput binary protein interaction mapping is continuing to extend our understanding of cellular function and disease mechanisms. However, we remain one or two orders of magnitude away from a complete interaction map for humans and other major model organisms. Completion will require screening at substantially larger scales with many complementary assays, requiring further efficiency gains in proteome‐scale interaction mapping. Here, we report Barcode Fusion Genetics‐Yeast Two‐Hybrid (BFG‐Y2H), by which a full matrix of protein pairs can be screened in a single multiplexed strain pool. BFG‐Y2H uses Cre recombination to fuse DNA barcodes from distinct plasmids, generating chimeric protein‐pair barcodes that can be quantified via next‐generation sequencing. We applied BFG‐Y2H to four different matrices ranging in scale from 25 K to 2.5 M protein pairs. The results show that BFG‐Y2H increases the efficiency of protein matrix screening, with quality that is on par with state‐of‐the‐art Y2H methods. Synopsis: Barcode Fusion Genetics‐Yeast Two‐Hybrid, a new technology allowing many‐by‐many screening of protein interactions in a single pooled assay, is presented. High‐quality interactions are identified in search matrices up to 2.5 million protein pairs in scale. Barcode Fusion Genetics (BFG) enables phenotypic analysis of millions of strains, each carrying two engineered loci. BFG is applied to perform highly multiplexed yeast two‐hybrid protein interaction assays (BFG‐Y2H). Protein interactions for ˜2.5 million protein pairs are tested in a single BFG‐Y2H run. The quality of BFG‐Y2H results is on par with current state‐of‐the‐art Y2H methods. Abstract : Barcode Fusion Genetics‐Yeast Two‐Hybrid, a new technology allowing many‐by‐many screening of protein interactions in a single pooled assay, is presented. High‐quality interactions are identified in search matrices up to 2.5 million protein pairs in scale.